Artritis reumatoide temprana (2010)
Early Reumathoid Arthritis.The classic diagnosis of rheumatoid arthritis by American College of Rheumatology criteria is insensitive for detecting early disease. If rheumatoid arthritis is diagnosed early, disease remission and prevention of radiological progression can be quickly achieved, with marked impact on mortality and quality of life of patients. The clinical involvement of metacarpophalangeal and metatarsophalangeal joints, morning stiffness more than 30 minutes and anti-cyclic citrullinated peptide antibodies, together with imaging methods like magnetic resonance imaging and ultrasound, constitute fundamental pillars of early diagnosis. Early treatment with disease-modifying antirrheumatic drugs and biological therapy can achieve clinical status close to non-disease. Key Words: Early diagnosis. Rheumatoid Arthritis. Therapeutics.